INDIAN REGULATIONS ON ETHICS AND THEIR IMPACT ON COURT CASE BACKLOGS - S. Chandra (BRICS Law Journal)
The paper aims to explore the role of ethics regulations on the backlog of cases in the state of Uttar Pradesh, India. There, there are many local practices which hinder the disposal of cases in the courts. The paper examines several, beginning with the theoretical training in ethics at the law schools and its impact in practice. The paper then explores the legal status of strikes and how they are conceived by lawyers in delaying the disposal of cases. Next it deals with adjournments in the courts and unravels the myriad frivolous reasons cited in seeking adjournments, as well as how, despite statutory limitations, courts succumb to the pressure of the Bar in granting them. The author echoes concern for creating transparency, efficiency and a system that inspires integrity, and argues for the need to rethink and redesign the whole system and create independent tribunals to enquire into lawyers guilty of professional misconduct.